A Theoretical Analysis of Smuggling: A Reply - Bhagwati, Jagdish N.; Hansen, Bent (Quarterly Journal of Economics, 1975)
Jagdish N. Bhagwati, Bent Hansen; A Theoretical Analysis of Smuggling: A Reply*, The Quarterly Journal of Economics, Volume 89, Issue 4, 1 November 1975, P